Análise do Índice de Vulnerabilidade Costeira no setor Oeste da Região Metropolitana de Fortaleza - Franco, Brunno Jansen (2021)
The coastal zone is an extremely energetic and rapidly changing environment, generating risks and disasters of both anthropogenic and natural origin, and erosion is one of the first and main responses to the unsteadiness of this environment. Thereby, the understanding of coastal vulnerability to erosion enables to better deal with the consequences generated by erosive processes and their aggravations. The present study aimed to assess the degree of vulnerability to erosion on beaches of the metropolitan region of Fortaleza's west coast, considering the current situation. The methodology was based on the calculation of a coastal vulnerability index (CVI) for three sectors in the study area, through an analytical formula obtained by the arithmetic mean of six indicators of vulnerability to erosion, namely: shoreline position (m/year), calculation of Normalized Difference Vegetation Index (NDVI) - obtained through data processing automation tools from the virtual library available through Google Earth Engine - beach morphology, dune field configuration, wave exposure, and coastal engineering structures - obtained by mapping a coastal cell in each sector comprising the beaches of Tabuba (sector 1), Pecém (sector II), and Taíba (sector III), supported with field survey to improve interpretation. Subsequently, these indicators were grouped into 3 degrees of intensity: high, moderate, or low vulnerability. The results indicate, considering the CVI, that 34% of the analyzed coastline (~60 km) is highly vulnerable to erosion events, 49.26% of the coast is moderately vulnerable, and only 16.02% have a low degree of vulnerability. As a standout, we can point out the analyzed coastline variation, which presented variation values of approximately -5 m/year (sector I), as well as regions with 8 m/year (sector II). Finally, the method employed provides support for decision-making on mitigating measures in relation to the indicators analyzed for the beaches studied.